UNDERSTANDING OF EARLY CHILDHOOD EDUCATION PRINCIPALS IN PALEMBANG CITY REGARDING THE PAUD ACCREDITATION MECHANISM - Utami, Febriyanti (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
The principals of early childhood education institutions are an important element in the education institutions and are responsible for improving school quality through early childhood education accreditation in teaching the eight educational standards. The purpose of this study is to describe the principals of early childhood education institutions in Palembang City comprehension of the early childhood education accreditation process. The approach used in the research is a quantitative approach through survey methods. Data collection uses Google Form. The respondents in this study were 41 principals of early childhood education institutions in Palembang City who came from 16 sub-districts. The study’s findings demonstrate that the understanding of principals of early childhood education institutions in Palembang City is quite good, as shown by 41 principals of early childhood education institutions, there are 85.37% of principals of early childhood education institutions who have participated in accreditation outreach activities, 92.68% of principals of early childhood education institutions have understood the flow of applying for accreditation. Understanding the requirements for applying for accreditation, both specific requirements and general requirements, there are 78.05% of principals of early childhood education institutions who have understood the special requirements documents and there are 4 standards in the general requirements which have been understood by the principals of early childhood education institutions as a whole or 100%. There are 87.80% principals of early childhood education institutions who are able to use the Sispena application. However, it was still found that several principals of early childhood education institutions in Palembang City experienced problems in the accreditation application process, namely 24.39%. The principals of early childhood education institutions need to increase their understanding of the accreditation mechanism so that they can make the accreditation process optimal.